Identification of a novel interspecific hybrid yeast from a metagenomic spontaneously inoculated beer sample using Hi‐C. Issue 1 (19th October 2017) - Smukowski Heil, Caiti; Burton, Joshua N.; Liachko, Ivan; Friedrich, Anne; Hanson, Noah A.; Morris, Cody L.; Schacherer, Joseph; Shendure, Jay; Thomas, James H.; Dunham, Maitreya J.
Abstract: Interspecific hybridization is a common mechanism enabling genetic diversification and adaptation; however, the detection of hybrid species has been quite difficult. The identification of microbial hybrids is made even more complicated, as most environmental microbes are resistant to culturing and must be studied in their native mixed communities. We have previously adapted the chromosome conformation capture method Hi‐C to the assembly of genomes from mixed populations. Here, we show the method's application in assembling genomes directly from an uncultured, mixed population from a spontaneously inoculated beer sample. Our assembly method has enabled us to de‐convolute four bacterial and four yeast genomes from this sample, including a putative yeast hybrid. Downstream isolation and analysis of this hybrid confirmed its genome to consist of Pichia membranifaciens and that of another related, but undescribed, yeast. Our work shows that Hi‐C‐based metagenomic methods can overcome the limitation of traditional sequencing methods in studying complex mixtures of genomes. Copyright © 2017 John Wiley & Sons, Ltd.